Motivational readiness of children to school in nuclear and single parent families - Ostrovska, Kateryna; Grabovska, Sophia (Journal of Education Culture and Society, 2020)
The aim of the paper is a comparison of psychological readiness of the child to go to school in nuclear and single parent families. To obtain the objectives of the paper the following methods were used: 1) methods “Two schools” by L.A Venger to identify the level of formation of internal position of the student; 2) the method “Motivational research studies in older preschoolers” by M.R. Ginsburg; 3) method “Pattern” by L.I. Tsehanskaya to determine the degree of development of skills training activities; 4) method “Graphic dictation” by D. El’konin to study the ability to follow adult instructions. The investigated group consisted of 40 students from first grade secondary school - 20 students from nuclear families (12 girls and 8 boys) and 20 students from single parent families (9 girls and 11 boys). As a result of qualitative, comparative and correlation analysis it was shown that readiness of children to go to school susbstantially depends on completness of their families. The children from families have a higher level of skill training and internal position than children from single parent families. This occurs because both parents pay more attention to the children in the forming of a willingness to learn in school. The studies have shown that in the group of children from nuclear families dominate the highest level of development of skills training activities, increased formation of internal positions and childrens social motivation. These indicators are the hallmarks of readiness to learn at school. Also, some recommendations to teachers are provided as for increase of motivation to learn in children from single parent families.